Impact HR Digitalization and Analytics Human Resources on Organizational Performance : A Review Literature - Patricia, Mia Christy; Kumandang, Cahyatih (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the impact of HR digitalization and human resource analytics on organizational performance. The study highlights how the adoption of human resource information systems (HRIS) enhances operational efficiency and data-driven decision-making. HR analytics significantly contributes to identifying and addressing workforce challenges, thereby improving organizational performance. However, challenges such as data quality, analytical competence, and managerial support must be addressed to maximize the benefits of HR analytics. The review underscores the importance of top management support and a data-driven organizational culture for successful HR analytics implementation. Limitations include reliance on existing literature and potential publication bias. Future research should empirically investigate the causal relationships between HR digitalization, HR analytics, and organizational performance across diverse cultural and economic contexts.